Use of dental services and associated factors among elderly in southern Brazil - Alexandre Emidio Ribeiro Silva; Caroline de Oliveira Langlois; Carlos Alberto Feldens (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2013)
OBJECTIVE : To analyze the use of dental services and associated factors among elderly treated at Family Health Units in southern Brazil. METHODS : This cross-sectional study evaluated 438 elderly attending Family Health Units in Pelotas, southern Brazil. Data were collected using a standardized questionnaire covering demographic and socioeconomic variables, in addition to information on time elapsed since their last dental visit. Explanatory variables were classified according to Andersen and Davidson's model. Clinical variables were obtained by a trained dentist. Multivariable Poisson regression models with robust variance were used to identify factors associated with the outcome. RESULTS : The prevalence of use of dental services in the last 3 years was 41.1% (95%CI 36.5 - 45.7). Multivariable analysis revealed that the probability of not using dental services was higher among individuals who self-assessed their general health as poor or very poor (Prevalence Ratio [PR] = 1.36; 95%CI 1.05 - 1.78), with less than 8 years of education (< 4 years: PR = 1.43; 95%CI 1.01 - 2.02; 4 to 7 years: PR = 1.43; 95%CI 1.00 - 2.04), users of alcohol (PR = 1.31; 95%CI 1.08 - 1.59), and those with no teeth (PR = 1.73; 95%CI 1.29 - 2.32). CONCLUSIONS : The low prevalence of use of dental services among elderly attending Family Health Units in Pelotas, especially among those with poor self-assessed general health, lower education level, and without teeth, indicate the need for public policies to improve social indicators and general health.